Peran Asbabun Nuzul Dalam Memetakan Teks Al-Makki Dan Al-Madani Sebagai Pendekatan Ulumul Qur'an - Meiva Putri Evandra; Hapijah; Felycia Ade Irawati; Zahra Vica Amelia; Aulia Azizah; Akhmad Dasuki (GHIROH, 2025)
This article reexamines the operational definitions and classification criteria of Makki/Madani in Qur'anic studies through systematic analysis of traditional interpretations and modern scholarship. It identifies five main indicators: asbab al-nuzul as chronological reference, revelation order across the prophetic era, audience context and legal content, thematic profiling (tawhid, legal norms, community development), and rhetorical style. The findings reveal that while fundamental definitions remain constant, deviations in indicators create borderline cases where Madani verses appear in Makki surahs and vice versa. To address this inconsistency, the paper proposes a weighted decision framework prioritizing chronological evidence (asbab al-nuzul and revelation order), followed by internal historical signals (post-Hijrah references), then thematic and stylistic markers. This framework enhances research reproducibility, reduces classification bias, and supports consistent Makki-Madani annotation for educational purposes and digital humanities projects requiring systematic Qur'anic text analysis.